Regression Test Case Minimization with Firefly based Algorithm - Singh, Ajmer; Vandana, Vandana; Singh, Rajvir (International Journal of Computer Sciences and Engineering, 2018)
Software testing process ordinarily expends no less than half of the aggregate cost required in programming advancement. Programming advancement associations spend significant part of their financial plan and time in testing related tasks. Software testing is an indispensable component in the Software Development Life Cycle (SDLC) and can outfit brilliant outcomes; if directed appropriately and successfully in an improved way. Lamentably, Software testing is frequently less formal and thorough than it ought to. Regression testing means to reveal all the undesired reactions of code corrections on rest of the code. Regression testing ensures that settling of programming deficiencies does not present whatever other issues, which were absent prior. Regression testing is iterative process, where size and manysided quality of experiments continues expanding. Along these lines, Optimization of experiments is profoundly sought to finish the regression testing inside settled time and cost limitations. Streamlining of experiments amid regression testing is an open research problem as there is no single procedure which can supersede every other system on all parameters. Along these lines, researchers ought to evolve new experiment minimization systems for regression testing to improve its feasibility in view of different parameters. This paper reports a work on building up a novel minimization procedure for regression testing utilizing firefly based optimization.